Biosimilars design and analysis of follow-on biologics - Chow, Shein-Chung, 1955- (Chapman & Hall/CRC biostatistics series, 2014)
"Biologic drug products are therapeutic moieties that are manufactured using a living system or organism. These are important life-saving drug products for patients with unmet medical needs. They also comprise a growing segment in the pharmaceutical industry. In 2007, for instance, worldwide sales of biological products reached $94 billion US dollars, accounting for about 15% of the pharmaceutical industry's gross revenue. Meanwhile, many biological products face losing their patents in the next decade"--